Influence of Job Insecurity, Job Stress and Salary Satisfaction on the Loyalty of Contract Employees in the Regional Government of Kepahiang Regency - Susanti, Pesi; Pareke, Fahrudin Js.; Nasution, Nasution (UNIB Press, 2024)
Organizations need a loyalty increase plan to avoid negative impacts that can occur due to low HR loyalty. This research aims to determine the influence of job insecurity, job stress and salary satisfaction on the loyalty of contract employees in the Kepahiang district government. The research method used was a quantitative approach with multiple linear regression analysis techniques, involving 290 contract employees in the Kepahiang district regional government as participants. The results of the research show that job insecurity has a significant effect on contract employee loyalty, work stress has no significant effect on contract employee loyalty, salary satisfaction has a significant effect on contract employee loyalty and simultaneously the variables of job insecurity, job stress and salary satisfaction have an effect on contract employee loyalty. contract employee in the local government of Kepahiang district.